2019
DOI: 10.1021/acs.molpharmaceut.8b00809
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of CSK-DEX-PLGA Nanoparticles for the Oral Delivery of Exenatide to Improve Its Mucus Penetration and Intestinal Absorption

Abstract: The oral absorption of exenatide, a drug for type 2 diabetes treatment, can be improved by using nanoparticles (NPs) for its delivery. To improve the mucus penetration and intestinal absorption of exenatide, we designed a block copolymer, CSKSSDYQC-dextran-poly­(lactic-co-glycolic acid) (CSK-DEX-PLGA), and used it for the preparation of exenatide-loaded NPs. The functionalized exenatide-loaded NPs composed of CSK-DEX-PLGA were able to target intestinal epithelial cells and reduce the mucus-blocking effect of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 54 publications
3
54
0
Order By: Relevance
“…The absorption mechanism of the NPs has not been reported, which may be an ideal material for oral drug delivery. In addition, other nanocarriers were internalized into Caco-2 cells by multiple endocytosis mechanisms,31 which reminds us that these nanocarriers may be also considered to improve the intestine absorption by oral administration 3234…”
Section: Resultsmentioning
confidence: 99%
“…The absorption mechanism of the NPs has not been reported, which may be an ideal material for oral drug delivery. In addition, other nanocarriers were internalized into Caco-2 cells by multiple endocytosis mechanisms,31 which reminds us that these nanocarriers may be also considered to improve the intestine absorption by oral administration 3234…”
Section: Resultsmentioning
confidence: 99%
“…We utilised fluorescently-labelled model polystyrene NP systems and achieved ligand (Tf) presentation on NP via physical adsorption. This produced Tf-NP of approximately 180 nm (Figure 2), which fall within the optimal size range for intestinal epithelial transport [6,20,27,28]. Furthermore, it was previously shown that following presentation as coating on the surface of NP via physical adsorption, Tf retains the ability to target and interact with TfR [29].…”
Section: Discussionmentioning
confidence: 95%
“…For instance, nanocarriers modified with the goblet cell-targeted peptide (CSKSSDYQC (CSK)), have demonstrated enhanced mucus penetrating characteristics, reduced mucus clearance as well as specific uptake into goblet cells. Studies demonstrate the CSK peptide enhanced nanocarrier uptake in the oral mucosa for the delivery of insulin or exenatide for the treatment of diabetes [ [178] , [179] , [180] , [181] ], as well as enhanced uptake of gemcitabine in intestinal goblet cells for the treatment of breast cancer after oral administration [ 182 ]. The combination of nanocarriers loaded with drug candidates focusing on the treatment of CoVs combined with such surface peptides could form a promising strategy for the nasal delivery towards CoV-infected epithelial cells.…”
Section: Therapeutic Interventions and Nanomedicine Strategiesmentioning
confidence: 99%